Kaitan Sosio-demografi dan Luaran Klinis pada Pasien Diabetes Melitus TIpe 2 (DMT2) di Rumah Sakit X di Pekanbaru - Ahmad Muhaimin Rosyadi; Reza Laila Najmi; Novtafia Endri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with a high global prevalence and is one of the leading causes of morbidity and mortality worldwide. Several sociodemographic factors, including age, sex, disease duration, educational level, and comorbidities, are believed to influence clinical outcomes in diabetic patients. This study aimed to analyze the association between sociodemographic characteristics and clinical outcomes among patients with T2DM. A cross-sectional study was conducted at Hospital X in Pekanbaru. The inclusion criteria were patients aged ≥18 years diagnosed with T2DM, receiving oral antidiabetic therapy for at least six months, and having complete medical records. Sociodemographic data were analyzed descriptively, and clinical outcomes were assessed based on HbA1c levels, categorized as “achieved” if HbA1c <7% and “not achieved” if ≥7%. The Chi-square test was used for statistical analysis. Of 95 patients, the majority were aged ≥45 years (84.2%), female (69.5%), and had a disease duration of ≥6 years (83.2%). Target HbA1c was more frequently achieved among female patients (60.6%), those aged ≥45 years (60%), with disease duration <6 years (75%), general educational level (60.2%), and without comorbidities (59.7%). However, no significant association was found between sociodemographic characteristics and achievement of HbA1c targets (p>0.05). Although certain sociodemographic groups tended to achieve better clinical outcomes, the study found no significant relationship between sociodemographic factors and clinical outcomes in T2DM patients. Further research considering lifestyle factors and pharmacological therapy is recommended.